How Do Households Discount over Centuries? Evidence from Singapore's Private Housing Market - Eric Fesselmeyer; Haoming Liu; Alberto Salvo (Institute for the Study of Labor (IZA), 2016)
We examine Singapore's fairly homogeneous private-housing market and show that new apartments on historical multi-century leases trade at a non-zero discount relative to property owned in perpetuity. Descriptive regressions indicate that new apartments with 825 to 986 years of tenure remaining are priced 4 to 6% below new apartments under perpetual ownership contracts that are otherwise comparable. We consider an empirical model in which asset value is decomposed into the utility of housing services and a second factor that shifts with asset tenure and the discount rate schedule. Exploiting the supply of new property with tenure ranging from multiple decades to multiple centuries, we estimate the discount rate schedule, restricting it to vary smoothly over time through alternative parametric forms. Across different specifications and subsamples, we estimate discount rates that decline over time and, accounting for the observed price differences, are of the order of 0.5% p.a. by year 400-500. The finding that households making sizable transactions do not entirely discount benefits accruing many centuries from today is new to the empirical literature on discounting and, with the appropriate risk adjustment, of relevance to evaluating climate-change investments.
Keywords: D61; G12; H43; Q51; Q54; R32; 330; discounting; social discount rate; declining discount rates; asset pricing; cost-benefit analysis; policy evaluation; long time horizon; climate change; real estate